Role of calpain in breast cancer and regulation of therapeutic response to targeted treatment - Pu, Xuan (2016)
The calpain system is a group of intracellular cysteine proteases. Dysregulated calpain activity, or mutation in calpain isoforms, as well as its endogenous inhibitor calpastatin, has been found to play an important role in tumorigenesis. The main aim of the current study is to explore the differential role of calpain family members in different breast cancer molecular subtypes; validate calpain-1 as a biomarker of trastuzumab response in HER2+ breast cancer patients; and explore the mechanisms by which calpain family regulates trastuzumab response in HER2+ cells.